The relationship between serum Relaxin concentrations and knee valgus - Gilmer, G. G.; Roberts, M. D.; Oliver, G. D. (International Journal of Sports Medicine, 2020)
Female athletes are at an elevated risk for tearing their anterior cruciate ligament, compared to their male counterparts. Though injury screening clinical tests and neuromuscular training programs have been widely implemented, injury rates remain high among female athletes. The purpose of this study was to examine the relationship between serum relaxin concentrations and knee valgus during three clinical tests (single leg squat, drop vertical jump, and single leg crossover dropdown). Twenty-two female athletes volunteered. Participants were scheduled for collection during the mid-luteal phase, when serum relaxin concentrations are known to be measurable. Blood samples were collected, and serum relaxin concentrations were quantified. Kinematic data were collected while participants performed the three clinical tests. Regression analyses revealed statistically significant relationships between serum relaxin concentrations and knee valgus throughout all tests. These findings suggest that serum relaxin concentrations and knee valgus are not independent of each other and more holistic approaches may be necessary to truly map out the risk for injury and ultimately reduce the rate of anterior cruciate ligament injuries. Thus, concluding that knee valgus, a highly utilized modifiable biomechanical risk factor, and relaxin, a hormone that has been associated with anterior cruciate ligament injury in female athletes, are related to each other.